Adaptive market hypothesis and momentum effect: Evidence from Dhaka Stock Exchange - Tahmina Akhter; Othman Yong (Cogent Economics & Finance, 2019)
This paper examines time-varying behavior of momentum and contrarian profits to identify the existence of adaptive market hypothesis (AMH), and whether AMH can provide justification for the presence of such anomalous behavior in the Dhaka Stock Exchange (DSE) of Bangladesh. To investigate the time-varying pattern of momentum/contrarian anomaly, the study uses stock prices of all listed companies on the DSE and values of DSE general index from January 1995 to December 2018. To construct the relative strength portfolios for momentum strategies, the current study employs the portfolio formation methods of Jegadeesh and Titman with minor modifications. The study findings suggest the existence of medium-term momentum profits and the long-term reversal effect that vary over time. Moreover, the empirical evidence of the study shows that the changed market conditions that are considered as the main reasons under AMH for time-varying behavior of market efficiency and by extension the stock market anomalies influence the momentum profits. The findings suggest that although market risk cannot always explain the existence of momentum profits in the DSE, the bullish stock market condition positively impacts this anomalous profit pattern. In addition, the momentum profits are not statistically significant during stock market crashes and bubbles, but the normal market condition positively influences the momentum profits. The most interesting finding of this study is that the investors from emerging stock markets may not adapt towards changed market conditions like the investors from the developed markets as reported in the AMH literature.
Keywords: 330; Adaptive market hypothesis (AMH); efficient market hypothesis (EMH); momentum effect; emerging stock market; Dhaka stock exchange